Evaluation of ELISA for the detection of rabies virus antibodies from the thoracic liquid and muscle extract samples in the monitoring of fox oral vaccination campaigns. Issue 1 (December 2016) - Bedeković, Tomislav; Šimić, Ivana; Krešić, Nina; Lojkić, Ivana; Mihaljević, Željko; Sučec, Ivica; Janković, Ivana; Hostnik, Peter
Abstract Background The main goal of oral vaccination of foxes is eradication of rabies in the red fox population as rabies reservoirs. To evaluate the success of vaccination a serological testing is conducted as a part of monitoring program. Two different methods are used regarding rabies serology: virus neutralisation test and ELISA. Methods In this study the reliability of BioPro ELISA was evaluated for testing haemolytic thoracic liquids and muscle extracts originated from 147 foxes in comparison to mFAVN. Also, the influence of heat treatment of samples on test results was investigated. Results The specificity of the test for not-heat treated samples was 92.98 % and sensitivity 79.20 %. Diagnostic validity of the ELISA compared to the mFAVN test when not-heat treated samples were used was 89.16 %. The specificity of the test for heat treated samples was 79.10 % and sensitivity 96.36 %. Diagnostic validity of the BioPro ELISA compared to the mFAVN test for heat treated samples was 94.30 %. Conclusion According to this study, the BioPro ELISA is reliable tool for detection of rabies specific antibodies in the context of evaluation of oral vaccination of foxes from poor quality samples as a substitution for virus neutralisation tests.